Polygonumperfoliatum L., an Excellent Herbal Medicine Widely Used in China: A Review - Liu, Junyu; Zeng, Yuanlian; Sun, Guojuan; Yu, Shaopeng; Xu, Yi; He, Chao; Li, Zulun; Jin, Shenrui; Qin, Xuhua (Frontiers in Pharmacology, 2020)
Polygonum perfoliatum L. (internationally accepted and only valid name; synonym: Polygonum knotweed L.; Persicaria perfoliata; family: Polygonaceae) is a kind of folk traditional Chinese medicine with a long history of widely use in the treatment of ancient internal, surgical and gynecological diseases. At present, 80 chemical constituents have been isolated from Polygonum perfoliatum L., including flavonoids, anthraquinones, terpenoids, phenolic acids, phenylpropanoids and alkaloids, among which flavonoids are the main active components. Modern studies have shown that Polygonum perfoliatum L. has pharmacological activities such as anti-inflammatory, anti-bacterial, antiviral, anti-liver fibrosis, antitussive and expectorant, anti-tumor, anti-oxidation and so on. By consulting and sorting out a large number of related literatures at home and abroad in recent years, this paper systematically reviewed the botany, traditional uses, phytochemistry, pharmacological activities and quality control of Polygonum perfoliatum L., and discussed its development potential in new drug research and clinical application in the future, in order to provide a reference basis for further research and promote the in-depth development and utilization.